2013
DOI: 10.1371/journal.pone.0074522
|View full text |Cite
|
Sign up to set email alerts
|

Grape Powder Intake Prevents Ovariectomy-Induced Anxiety-Like Behavior, Memory Impairment and High Blood Pressure in Female Wistar Rats

Abstract: Diminished estrogen influence at menopause is reported to be associated with cognitive decline, heightened anxiety and hypertension. While estrogen therapy is often prescribed to overcome these behavioral and physiological deficits, antioxidants which have been shown beneficial are gaining nutritional intervention and popularity. Therefore, in the present study, utilizing the antioxidant properties of grapes, we have examined effect of 3 weeks of grape powder (GP; 15 g/L dissolved in tap water) treatment on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 63 publications
12
55
0
1
Order By: Relevance
“…Regarding the antioxidant enzymes, some studies showed decreased activities (Abbas et al 2011) while others reported no changes in their levels (Dilek et al 2010). The behavioral changes observed were also comparable with previous studies which reported anxiety-like behavior and inhibitory effect on locomotion after ovariectomy in rats (Patki et al 2013). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the antioxidant enzymes, some studies showed decreased activities (Abbas et al 2011) while others reported no changes in their levels (Dilek et al 2010). The behavioral changes observed were also comparable with previous studies which reported anxiety-like behavior and inhibitory effect on locomotion after ovariectomy in rats (Patki et al 2013). …”
Section: Discussionsupporting
confidence: 90%
“…Several studies found a correlation between the estrogen depletion and the increased OS level in women Several changes in the brain antioxidant profile were also identified in menopause: reduced GSH/GSSG ratio (Abbas and Elsamanoudy 2011;Dilek et al 2010), increased MDA levels (Abbas and Elsamanoudy 2011) and high levels of nitrated proteins (Patki et al 2013). It seems that hippocampus is the most susceptible region to ovariectomy-induced estrogen depletion, in terms of generation of oxidative stress (Patki et al 2013). We have also observed enhanced MDA levels in the hippocampus of the ovariectomized rats, especially 21 days after the ovariectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems that a high level of endogenous estrogen attenuates anxiety and depression like behaviors. The results of present study confirm the mood improvement effects of endogenous ovarian hormones 19 . It has also been previously shown that female mice in proestrus have better moods than those in other phases 20 .…”
Section: Discussionsupporting
confidence: 89%
“…For example, hippocampus, amygdala, and cerebellar granule cells have been reported as the most susceptible to oxidative stress in some studies (Wang and Michaelis, 2010), and consequently are purported to be the first to undergo functional decline. Our own preclinical work has suggested that behavioral and cognitive deficits are attributed to three brain regions: hippocampus, amygdala, and prefrontal cortex (PFC) (Masood et al, 2008;Salim et al, 2010aSalim et al, ,b, 2011aPatki et al, 2013a;2013b;Solanki et al, 2015). Hippocampus seems to be at the hot seat, and it appears that this brain region undergoes major biochemical changes that ultimately determine neuronal connections and function.…”
Section: Oxidative Stress and The Brainmentioning
confidence: 99%